Relationship between serum progesterone levels at the day before progesterone suppository administration and pregnancy rate in embryo transfer cycles - Farahnaz Farzaneh; Ahmad Ahmadian Shalchi; Saeedeh Sarhadi (Mashhad University of Medical Sciences, 2021)
Introduction: Given the importance of assisted reproductive therapies and achieving a pregnancy leading to live birth, as well as the importance of the used treatments and the various studies which have been performed so far, this study was performed with aim to evaluate the relationship between endometrial pattern and serum progesterone levels at the day before the onset of progesterone suppository in embryo transfer cycles in women referred to Infertility Center of Zahedan. Methods: This cross-sectional study was performed on 50 women who had undergone IVF for any reason and their embryos were frozen in infertility center of Zahedan University of Medical Sciences in 2019. The patients were treated with progesterone suppository 400 mg at morning and 400 mg at evening intra rectally. Demographic data, endometrial pattern and thickness ultrasound, serum progesterone level at the day before the onset of progesterone suppository and serum BHCG levels 14 days after embryo transfer were recorded. Data were analyzed by SPSS statistical software (version 24) and Chi-square and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: IVF outcome was positive in 13 cases (26%). 23 patients (46%) had homogenous endometrial pattern and 27 (54%) had three-line pattern. Serum progesterone level were significantly lower in patients who had positive BHCG than patients who had negative BHCG (p <0.001). Conclusion: Among women undergoing IVF, serum progesterone levels and also endometrial pattern (homogenous or three-line) was different. Serum progesterone level before the onset of treatment was related to the pregnancy outcome (positive or negative), as well as in women with lower progesterone levels   in day before the start of progesterone suppositories, treatment with progesterone suppository could lead to better pregnancy outcomes following IVF, which is a novel and important finding.